Teak takes off - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Teak is in fashion these days, with public and private bodies in several countries investing in plantations of the Tectona grandis tree and small farmers getting interested too. The tree grows easily: with a lot of light, and well drained soils, it...